increasing students' interest in reading with a cooperative learning model of think pair share type in grade 1 students of muruh 2 elementary school in gantiwarno, klaten district - Suyanti, Suyanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The importance of efforts to increase students' interest in reading is focused on teacher actions at school. At SD Negeri Muruh 2 the teaching and learning process planned by the teacher uses several methods that can increase students' interest in reading. The cooperative learning model with the think pair share type is one of them. This learning model adds variety to interesting learning at school. Students become more active and enthusiastic in carrying out learning. The cooperative learning model with the think pair share type provides opportunities for students to think independently in pairs, thus increasing students' enthusiasm for learning to read. The results of classroom action research show that through the implementation of learning using the cooperative learning model with the think pair share type, students are more active, enthusiastic and interested in reading activities. Data shows a 25% increase in interest in reading for grade 1 students at Muruh 2 Public Elementary School. In cycle 1, only 65% of students appeared active and 70% of students passed the evaluation questions. In cycle 2, 95% of students were active and 95% of students passed the evaluation questions. The cooperative learning model with the think pair share type is effective in increasing the reading interest of grade 1 students at Muruh 2 Public Elementary School.